Współczesne znieczulenie w chirurgii zaćmy - Kałużny, Józef; Kałużny, Bartłomiej (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
The aim of this paper is, to present methods of anesthesia in contemporary cataract surgery (phacoemulsification). The autors described operation without anesthesia, topical drop, topical drop plus lidocaine into anterior chamber, peribulbar anesthesia. Retrobulbar and general anesthesia are also mentioned.